ESG controversies and banking performance: The moderating effect of board activity - Mahyoub, Mugahed; Ja’afar, Roslan; Ghani, Nur Laili Ab (Asian Economic and Financial Review, 2024)
The present study examines the influence of ESG controversies on the financial performance of listed banks in the Asia-Pacific region (APAC). The nexus between environmental, social, and governance (ESG) metrics and financial performance has garnered significant attention from academics, corporations, executives, and regulators in the present era. In addition, this study investigates whether board activity moderates the relationship between ESG controversies and bank performance. This study adopts a quantitative approach and employs a cross-country sample of 54 banks with 540 bank-year observations from 2013 to 2022. The data were compiled from the London Stock Exchange Group (LSEG) database and examined using panel data regression techniques. The findings indicate that the ESG controversies have a notable adverse effect on the performance of banks, as measured by Tobin's Q. Interestingly, the study discovered that board activity alleviates the negative influence of ESG controversies on bank performance. These empirical findings aid investors and managers in assessing the impact of ESG controversies and board activity on bank performance. Moreover, the empirical findings can aid bank managers in implementing a proactive governance-oriented approach. Particularly, board activity should be regarded as a method to reduce the negative effects of ESG controversies on performance.